96.3k views
1 vote
Factor completely. x^2-3x-28

2 Answers

3 votes

Answer:

(x-7)(x+4)

Explanation:

We have given an expression.

x²-3x-28

We have to factorize given expression.

Split the middle term of above expression so that the sum of two term should be -3 and their product be -28.

x²-7x+4x-28

Making groups and taking common , we have

x(x-7)+4(x-7)

Taking (x-7) as common, we have

(x-7)(x+4) which is the answer.

User Claude COULOMBE
by
6.1k points
5 votes

Answer:

= (x+4) (x-7)

Explanation:

x²-3x -28

Product = -28

Sum = -3

numbers = -7 and 4

Thus;

x²- 3x -28 ; replacing -3x with -7x and 4x

x²-7x +4x -28

x(x-7) + 4(x-7)

= (x+4) (x-7)

User Albert Schilling
by
5.3k points